Auditoría de gestión al proceso de apoyo: talento humano de la Unidad Educativa Fiscomisional Calasanz de la ciudad de Loja, período 2016 - Macas Parra, Glenda Maritza (2019)
This paper entitled "MANAGEMENT AUDIT FOR THE SUPPORT PROCESS: HUMAN TALENT OF THE CALASANZ FISCOMISIONAL EDUCATIONAL UNIT OF THE CITY OF LOJA, PERIOD 2016", is oriented to the application of the management audit, to establish the degree of control that maintains the Educational Unit in the administrative and operational activities, through the application of the internal control questionnaire and indicators that allow to measure the efficiency and effectiveness with which the resources are handled, it also allows to verify the compliance of Laws, Norms and Regulations in the development of activities and issue a report containing comments, conclusions and recommendations that must be met to provide a quality education. Likewise, each of the Audit phases was developed, the methodology that was used was; a previous visit to the institution subject to the audit, where the technique of interviewing the Human Talent of the component to be evaluated was carried out, which helped to collect information related to its management, which facilitated the audit program and determined the procedures to be used, management indicators were also applied that allowed to establish the level of efficiency, effectiveness and quality, achieving an analysis of the situation in which the institution is in relation to the management carried out by Human Talent, This allowed us to verify that 5 there are no significant findings, and that the institution is in a very good rating range in terms of management and development of both administrative and academic activities. As a result of the audit, the respective Final Report is prepared and submitted to the Rector and other Authorities of the Educational Unit, which includes comments, conclusions and recommendations that will serve to strengthen the internal control system. institutional management with sufficient and timely information to improve institutional management and that the activities developed by Human Talent so that thanks to the recommendations can be performed in full and efficiently and effectively, in order to provide an educational service of excellence and quality